Cameroon - Fiscal policy for growth and development - World Bank (World Bank, 2012)
Cameroon's growth achievement is disappointing and the country is not likely to meet most of the Millennium Development Goals (MDGs) on its current trajectory. Underemployment is extremely high, with risks of social unrest and instability. The fallout of the current global economic crisis is making more challenging the attainment of growth targets foreseen in the new Growth and Employment Strategy (DSCE) and in the new vision 2035. This overall picture hides an even more worrisome divide between urban and rural areas, among provinces, and between farmers and all other socioeconomic groups. Cameroon has ended up in this situation as a result of several factors, including a legacy of poor public finance management, weak governance, and inequitable distribution of resources. The report also argues that the Government has the capacity to use fiscal policy as an effective instrument to address the legacy, governance, and distribution issues that are constraining growth, while providing basic services and necessary public goods to the population. The Government is committed to reviving growth and job creation, in line with vision 2035, and the recommendations in this report could help it to achieve these goals. The Government needs to act quickly, however, as the costs of delaying reforms can be high. It also needs to engage with the private sector, for example, in public private partnerships in the energy sector.